Promise and despair the first struggle for a non-racial South Africa - Plaut, Martin 1950- (Ohio University Press, 2017)
Setting sail -- South Africa's troubled century -- Scorched earth and broken promises -- From war to Union -- London: friends and allies -- London: campaigning for non-racialism -- London: the parliamentary struggle -- London: Gandhi's campaign -- 'The blow has fallen': the reality of Union -- Gandhi: defeat and victory -- Aftermath: the road to war -- Conclusion -- Appendix: franchise timeline